Applying the developmental model of intercultural sensitivity to measure student growth after an on-campus intervention in Japan - Wang, Hui Ling (Journal of International Students, 2026)
This study sought to determine whether the DMIS could be used to measure on-campus intervention efforts among Japanese university EFL students regarding IS. The literature review explains IC measurement in overseas study programs and local educational interventions, summarizes the diagnosis of the six stages of the DMIS, and explores its use in IS measurement studies. A hybrid approach of content and thematic qualitative analysis of reflective writings was used to determine how students in two intercultural communication courses developed along the stages of the DMIS. The study revealed that participants demonstrated personal growth in intercultural awareness, that their self-reflections hinted at the stages of the DMIS, and that they were generally accurate in their self-assessment.